Graphing calculator exposure of mathematics learning in a partially technology incorporated environment - Kharuddin, Azrul Fazwan; Ismail, Noor Azina (Eurasia, Gazi University, 2017)
Integrating technology in the mathematics curriculum has become a necessary task for curriculum developers as well as mathematics practitioners across the world and time. In general research studies seeking a better understanding of how best to integrate mathematics analysis tools with mathematics subject matter normally observe mathematics lessons taught exclusively in a technology enriched environment or computer lab. In some universities where paper and pencil examination is the major assessment tool, undergraduate mathematics courses are still taught in a traditional manner that takes care of the algorithmic and procedural steps. This paper relates a study that embarks on the technology exposure claiming that human action is mediated by technological setting. Situated in a traditional classroom setting where there is more teaching and less hands-on, it reports foundation students’ acceptance of technology-in-mathematics interaction in a typical course enriched with graphing calculator (GC) deliberated in the worksheets with printed GC commands alongside each question. Data was collected from students’ worksheets and also questionnaire that measures attitudes towards technology in mathematics from a class of 763 pre-university students. The results may enlighten mathematics practitioners about the feasibility of taking full advantage of technology to teach mathematics in a partially technology incorporated mathematics course